2022
DOI: 10.1002/mrm.29168
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac MR imaging (ICMRI) guiding‐sheath with amplified expandable‐tip imaging and MR‐tracking for navigation and arrythmia ablation monitoring: Swine testing at 1.5 and 3T

Abstract: Purpose Develop a deflectable intracardiac MR imaging (ICMRI) guiding‐sheath to accelerate imaging during MR‐guided electrophysiological (EP) interventions for radiofrequency (500 kHz) ablation (RFA) of arrythmia. Requirements include imaging at three to five times surface‐coil SNR in cardiac chambers, vascular insertion, steerable‐active‐navigation into cardiac chambers, operation with ablation catheters, and safe levels of MR‐induced heating. Methods ICMRI’s 6 mm outer‐diameter (OD) metallic‐braided shaft ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…Custom-made actively tracked needles (incorporated a receiver antenna) have been described to enable transseptal puncture under real-time CMR guidance[ 55 ]. Recently, a deflectable intracardiac MRI-compatible guiding-sheath was developed to accelerate imaging during CMR-guided electrophysiological interventions while real-time CMR-guided pericardiocentesis using commercially available passive access titanium needles has also been described[ 56 , 57 ].…”
Section: Clinical Implementation Of Cmr-guided Ablationmentioning
confidence: 99%
“…Custom-made actively tracked needles (incorporated a receiver antenna) have been described to enable transseptal puncture under real-time CMR guidance[ 55 ]. Recently, a deflectable intracardiac MRI-compatible guiding-sheath was developed to accelerate imaging during CMR-guided electrophysiological interventions while real-time CMR-guided pericardiocentesis using commercially available passive access titanium needles has also been described[ 56 , 57 ].…”
Section: Clinical Implementation Of Cmr-guided Ablationmentioning
confidence: 99%
“…41 An example of such T1w-imaging sequence is TWILITE (T1w long inversion time), which is a promising method for the acute detection of ablation lesions without the need for a contrast agent (Figure 1D). 42,43 Given the high resolution imaging that is required to visualize the thin atrial wall, techniques to enhance the signal to noise ratio of non-CAE T1w-images will be paramount for utility in clinical practice.…”
Section: Non-contrast Agent Enhanced T1-weighted Imagingmentioning
confidence: 99%
“…Schmidt and colleagues successfully executed a real-time MRI-guided ablation in the RA-and LA roof of a swine model, and subsequently performed TWILITE imaging and histological examination. 43 Visual comparison revealed that the ablation procedure created both continuous and spaced lesions. However, since lesion size was not assessed quantitatively, the reliability of TWILITE in real-time lesion evaluation could not be confirmed.…”
mentioning
confidence: 99%